Pengaruh Rating dan Online Customer Review terhadap Keputusan Pembelian Skincare pada Aplikasi Marketplace Shopee di Surabaya - Soviatun Lailih; Komarun Zaman; Nur Hidayah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
In Indonesia, the growth of e-commerce, particularly in the skincare sector, is driven by advances in digital technology. Features such as ratings and online customer reviews have become important components in customer decisions about online shopping. The purpose of this study was to determine how ratings and online customer reviews influence people's decisions in Surabaya City to purchase facial care products through the Shopee application. The respondents in this study were 45 active Shopee customers who had purchased facial care products. Data were collected through a Likert-based questionnaire, and the SPSS program was used to analyze multiple linear regression. The results showed that the rating and online customer reviews variables had a significant influence simultaneously on purchasing decisions, but only online customer reviews had a significant influence partially. These results emphasize that informative and reliable review content is more important than rating value alone in building trust and influencing customer purchasing decisions.